ANALISIS DANA PIHAK KETIGA TERHADAP KEUNTUNGAN BUNGA BERSIH PADA PT BANK RAKYAT INDONESIA - Adinda Noor Azizah Kusnendar (2022)
Currently, the banking industry is experiencing a fairly rapid development. Thus, competition to attract public interest is also getting tougher, so all banks must have creative and innovative corporate management strategies in offering and introducing their products to the public. With a good strategy, the public will entrust the bank in storing funds, borrowing funds, and using these banking products. The higher the growth of third party funds in the bank, the greater the loan disbursement provided by the bank. The collection of third party funds will incur interest costs that must be incurred by the bank, while the distribution of loans will generate interest income for the bank which will result in the growth of profits generated. In this case, to see a banking performance through a description or description of the use of third party funds in generating net interest income at PT Bank Rakyat Indonesia. All data obtained in the report is through the annual report of PT Bank Rakyat Indonesia. Keywords: Third Party Funds (TPF), Interest Income, Interest Fees